Introduction to reference sources in the health sciences - Roper, Fred W. (Medical Library Association, 1980)
Guide to bibliographic and informational sources and their uses in reference work in health science settings. Intended for the library school student, but also useful to practicing librarians and health science library users. Fourteen chapters cover such topics as bibliographic sources for monographs, computerized data bases, handbooks and manuals, and history sources.